THE APPLICATION OF ACCOUNTABILITY PRINCIPLES IN THE PROVISION OF FREE EDUCATION IN GOWA REGENCY - RATIH ISTIQOMAH RAUF; HAMZAH HALIM; HASBIR PASERANGI (Awang Long Law Review, 2022)
The purpose of writing this paper is to analyze the principle of accountability in the provision of free education Gowa Regency Regulation Number 4 of 2008 and Gowa Regency Regional Regulation Number 9 of 2013. This study uses a sociojuridical research type, using a statutory approach and a conceptual approach. The data used are primary data and secondary data obtained through interviews and literature study, the data collected is then analyzed qualitatively. The results of the study indicate that the principle of accountability as one of the main principles of good governance has been implemented by the Gowa Regional Government in providing free education in Gowa Regency. This is evidenced by the existence of the Gowa Regency Regional Regulation Number 4 Year 2008 concerning Free Education and the Gowa Regency Regional Regulation Number 9 Year 2013 concerning Amendments to the Gowa Regency Regulation Number 10 Year 2009 concerning the Compulsory Education Program, the two provisions of the legislation in the form of Regional regulations and Regent's Regulations have become a guarantee of accountability for the provision of free education in Gowa Regency.